Perspectivas e processos de organização do texto: caminhos para o trabalho com a língua portuguesa em sala de aula - Marson, Camila (2020)
Starting from the alarming results of children and young people in internal and external evaluations – in regard to reading, interpretation and textual production –, as well as the publication of a new normative document for the schools in the country, the Common Curriculum National Base (CCNB), the present dissertation aims to establish, to the teacher, a way of conducting mother tongue teaching that is guided by the experience of language, and that conducts teaching-learning actions for the effective use of language. As already anticipated in the National Curriculum Parameters (NCP), the CCNB also considers that the focus of language work in the classroom should be anchored and developed from the text. The research proposed here makes use of scientifically supported analysis instruments, in particular, the functionalist theory of language, in order to provide safe support points when conduction the text work in the classroom. Specifically, it aims to examine linguistic uses according to discursive genres by which the constitution of texts is based, and how the processes involved in statement constitution determine the construction of meanings, given that, by such procedures, discursive genres are configured. The basic process of text constitution, the predication, is analyzed in the newspaper headline genre, considering that its condensed structure is constituted prototypically of a predication. The conclusions reach some prototypical “slips” or typological “hybridizations” of the texts under analysis, that serve as a universe of possibilities for the teacher to develop meaningful text practices in the classroom, directing students‟ eyes to these questions.